Reflexões acerca do significado nas obras de ficção de José Saramago - José Barbosa Machado (Confluenze, 2023)
With this essay, we intend to study one of the particularities of José Saramago’s style that has escaped those who have been studying his work: reflection on writing itself and, more specifically, on the matter of language, that is, the words he uses and their meanings. The writer often goes on a series of wanderings, in which he reflects on the semantic properties of certain words or expressions, a rare or even non-existent process in other Portuguese writers.